(untitled) (Journal of Environmental Microbiology and Toxicology, 2024)
model being one of the most commonly used due to its simplicity and requiring only a few parameters. Temperature is a key factor that impacts microbial growth and their metabolic activities on various substrates. Because of their small size, microorgan-isms are very sensitive to the changes in environmental temperatures. The growth behavior of Rhodotorula sp. strain MBH23 on acrylamide reveals a unique chevron-like pattern in apparent activation energy, with a notable breakpoint at 28.05°C. The analysis revealed two distinct ranges for activation energy: 32–40°C with a value of 60.66 kJ/mol and 20–27°C with 51.60 kJ/mol. Within the 32–40°C range, the Q₁₀ value, which measures the rate of reac-tion change with temperature, was found to be 2.15, while the theta value, indicating the temperature coefficient, was 1.08. These findings offer important insights into how acryla-mide breaks down and moves, particularly in the context of bioremediation efforts. Study provides valuable insights for predicting acrylamide degradation and its movement during bioremediation processes.